The restoration of Gregorian chant : Solesmes and the Vatican edition - Combe, Pierre (Catholic University of America Press, 2003)
Publisher's description: This book presents for the first time in English the fully documented history of the Gregorian chant restoration which culminated in the publication of the Vatican Edition ordered by Pope Pius X at the dawn of the twentieth century. It is based upon archival documents in the Abbey of St. Pierre de Solesmes. The ecclesia orans, the Praying Church, has always regarded genuine church music as an integral part of prayer and of solemn public worship as a whole. Sacred music is not intended to beautify and decorate worship. Rather, taking shape from the depths of the Church's interior life, sacred music bears the imprint of that divine beauty which never grows old--and which is far more sublime than all mere artistic or historical intentions. Gregorian chant, the Catholic Church's very own music, is proper to the Roman liturgy, but during the course of its long history it has experienced periods of ascendancy and of decline. A century ago, Pope Pius X called for a restoration of the sacred melodies, and the result was the Vatican Edition. This book describes in careful, vivid detail the strenuous efforts of personalities like Dom Joseph Pothier, Dom Andre Mocquereau, Fr. Angelo de Santi, and Peter Wagner to carry out the wishes of the Pope. The attentive reader will not fail to note that many of the questions so fervidly debated long ago are still current and topical today. The original French edition, Histoire de la restauration du chant grǧorien, was published by the Abbey of Solesmes in 1969. Robert A. Skeris's new introduction to this edition illuminates the current discussion with documentation including the Preface to the Vatican Gradual and the "Last Will and Testament" written by Dom Eugene Cardine. Dom Pierre Combe, O.S.B., (1913-1993) was a monk and archivist of the Abbey of Solesmes. +Theodore Marier, world renowned scholar and composer, was Justine Bayard Ward Professor and Director of the Center for Ward Studies at The Catholic University of America. William Skinner, a former student of Dr. Marier's, is a professional translator and interpreter.